1988
DOI: 10.1159/000288121
|View full text |Cite
|
Sign up to set email alerts
|

Attempted Suicide in Psychiatric Outpatients with Concurrent Physical Illness

Abstract: Fifty outpatients with concurrent psychiatric and physical illness who were referred following a suicidal attempt to the Outpatient Psychiatric Department, University of Athens, during a period of 3 years (1979–1981) were compared with a random sample of 85 psychiatric outpatients without concurrent physical illness who had attempted suicide at the same time period. Attempters suffering from both mental and physical illness were more often of an older age, married, pensioners or housewifes, were living with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 7 publications
2
9
0
1
Order By: Relevance
“…In the group not interviewed the so matically ill did only differ significantly from the not somatically ill with respect to age. The higher age and BDI score in patients with a somatic disease is consistent with the results of the earlier mentioned investigation of suicide attempters with and without a so matic disease [ 17], It was found in the investi gation that patients with a somatic disease were older and more often had an affective disorder. Furthermore, in contrast to the present study, the somatically ill were more often psychotic or had an affective disorder.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…In the group not interviewed the so matically ill did only differ significantly from the not somatically ill with respect to age. The higher age and BDI score in patients with a somatic disease is consistent with the results of the earlier mentioned investigation of suicide attempters with and without a so matic disease [ 17], It was found in the investi gation that patients with a somatic disease were older and more often had an affective disorder. Furthermore, in contrast to the present study, the somatically ill were more often psychotic or had an affective disorder.…”
supporting
confidence: 90%
“…An increase in the risk of attempted suicide has been seen in connection with e.g., mi graine and epilepsy [14][15][16], A comparison has been made [ 17] of suicide attempters with concurrent psychiatric and somatic disease and suicide attempters with a psychiatric dis ease alone. It has shown that attempters suf fering both from a somatic and psychiatric disease were found to be older, more often suffered from an organic psychotic condition or affective disorder, and more frequently used violent methods in the attempt.…”
Section: Introductionmentioning
confidence: 99%
“…These were often consistent with known risk factors, including physical and psychiatric health complaints(2224), daily stimulant use(17), violent behavior(19), and previous SI or SA(23). After controlling for overlap among risk factors through multiple logistic regression, the SI and SA were both predicted by past 30-day SI and lifetime SA, while SI was additionally predicted by EuroQol depression/anxiety and SA was additionally predicted by difficulties with violent behavior.…”
Section: Discussionmentioning
confidence: 55%
“…These clinics were part of a large, urban medical center and were considered safety-net clinics in that they served a large number of patients who are low-income and have limited or no health insurance. Few patients in this setting formally seek substance use treatment, and many patients have several suicide risk factors (e.g., high rates of physical and psychiatric illness(2224), low-income and/or unemployment(25), homelessness, and prior SI and SA(23,26)).…”
Section: Methodsmentioning
confidence: 99%
“…people with an episode of depression are more likely to develop an episode of MUS and those with MUS are more likely to develop an episode of depression 7 . It should be remembered that most conditions resulting in physical symptoms, especially when they include pain and disability, place the sufferer at an elevated risk of depression, which will worsen the prognosis in a variety of physical conditions 8 . The interplay between what we often assume to be separate physical and mental symptoms is complex and may simply reflect a basic interconnectivity of physical and mental states.…”
Section: What Is Known About Gynaecological Mus?mentioning
confidence: 99%